Exploration of the feasibility to combine patients with chronic obstructive pulmonary disease and chronic heart failure in self-management groups with focus on exercise self-efficacy - Maaike Giezeman; Kersti Theander; Ann-Britt Zakrisson; Josefin Sundh; Mikael Hasselgren (Scandinavian Journal of Primary Health Care, 2022)
AbstractObjective To compare the level of exercise self-efficacy, symptoms, functional capacity and health status and investigate the association between these variables in patients with chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF). Additionally, to investigate how diagnosis, symptoms and patient characteristics are associated with exercise self-efficacy in these patient groups.Design Cross-sectional study.Setting Primary care.Subjects Patients (n = 150) with COPD (n = 60), CHF (n = 60) and a double diagnosis (n = 30).Main outcome measures Swedish SCI Exercise Self-Efficacy score, modified Medical Research Council Dyspnea score (mMRC), fatigue score, pain severity score, Hospital Anxiety and Depression Scale, functional capacity measured as six-minute walking distance and health status measured by a Visual Analogue Scale.Results Levels of exercise self-efficacy, health status and symptoms were alike for patients with COPD and patients with CHF. Functional capacity was similar after correction for age. Associations with exercise self-efficacy were found for slight dyspnea (mMRC = 1) (R −4.45; 95% CI −8.41– −0.50), moderate dyspnea (mMRC = 2) (−6.60;−10.68– −2.52), severe dyspnea (mMRC ≥ 3) (−9.94; −15.07– −4.80), fatigue (−0.87;−1.41– −0.32), moderate pain (−3.87;−7.52– −0.21) and severe pain (−5.32;−10.13– −0.52), symptoms of depression (−0.98;−1.42– −0.55) and anxiety (−0.65;−0,10– −0.32), after adjustment for diagnosis, sex and age.Conclusion and implications Patients with COPD or CHF have similar levels of exercise self-efficacy, symptoms, functional capacity and health status. More severe symptoms are associated with lower levels of exercise self-efficacy regardless of diagnosis, sex and age. When forming self-management groups with a focus on exercise self-efficacy, it seems more relevant to consider level of symptoms than the specific diagnosis of COPD or CHF.Key pointsExercise training is an important part of self-management in patients with COPD and chronic heart failure (CHF). High exercise self-efficacy is required for optimal exercise training.Patients with COPD and CHF have similar symptoms and similar levels of exercise self-efficacy, functional capacity and health status.Not the diagnosis, but symptoms of dyspnea, fatigue, pain, depression and anxiety are important factors influencing exercise self-efficacy and need to be addressed.When forming self-management groups with a focus on exercise self-efficacy, it seems more relevant to consider the level of symptoms than the specific diagnosis of COPD or CHF.